Are working memory and glutamate concentrations involved in early‐life stress and severity of psychosis?. Issue 6 (9th May 2020) - Corcoran, Mark; Hawkins, Emma L.; O'Hora, Denis; Whalley, Heather C.; Hall, Jeremy; Lawrie, Stephen M.; Dauvermann, Maria R.
Abstract: Objective: Occurrences of early‐life stress (ELS) are associated with the severity of psychotic symptoms and working memory (WM) deficits in patients with psychosis (PSY). This study investigated potential mediation roles of WM behavioral performance and glutamate concentrations in prefrontal brain regions on the association between ELS and psychotic symptom severity in PSY. Method: Forty‐seven patients with PSY (established schizophrenia, n = 30; bipolar disorder, n = 17) completed measures of psychotic symptom severity. In addition, data on ELS and WM performance were collected in both patients with PSY and healthy controls (HC; n = 41). Resting‐state glutamate concentrations in the bilateral dorsolateral prefrontal cortex (DLPFC) and anterior cingulate cortex (ACC) were also assessed with proton magnetic resonance spectroscopy for both PSY and HC groups. t tests, analyses of variance, and regression analyses were utilized. Results: Participants with PSY reported significantly more ELS occurrences and showed poorer WM performance than HC. Furthermore, individuals with PSY displayed lower glutamate concentrations in the left DLPFC than HC. Neither ELS nor WM performance were predictive of severity of psychotic symptoms in participants with PSY. However, we found a significant negative correlation between glutamate concentrations in the left DLPFC and ELS occurrence in HC only. Conclusion: In individuals with PSY, the current study found no evidence that the association between ELS and psychotic symptoms is mediated by WM performance or prefrontal glutamate concentrations. In HC, the association between ELS experience and glutamate concentrations may indicate a neurometabolite effect of ELS that is independent of an illness effect in psychosis. Abstract : This study investigated mediation roles of working memory performance and glutamate concentrations in prefrontal brain regions on the association between the occurrence of early‐life stress and symptom severity in individuals with schizophrenia and bipolar disorder. Our findings of reduced glutamate concentrations in the left dorsolateral prefrontal cortex and poorer working memory performance in patients with bipolar disorder, but not schizophrenia, may be useful for improved diagnosis in psychosis and treatment.